Accounting Students Learning Style In 4.0 Industrial Revolution Era: A Phenomenology - Primasa Minerva Nagari (AIBPM Publisher, 2019)
This study aims to describe the learning style of accounting students in the 4.0 industrial revolution era which is seen from the meaning of 4.0 Industrial Revolution Era and revealing that meaning to the learning style of accounting students. This study uses a qualitative descriptive method with a phenomenology approach to reveal the meaning of the 4.0 Industrial Revolution Era so as not to interfere with other perceptions outside the subject's self. The subjects in this study were four accounting students. The research data was collected using interview methods, documentation, and observation. The results of this study conclude that the meaning of the industrial revolution 4.0 era for accounting students is a time when all information can be easily obtained without any space and time limits. According to accounting students, this era greatly influenced their learning styles, because with this era the way to get the latest material and information about the subjects can be done very easily anywhere and anytime.